Charging Properties and Particle Dynamics of Chang’e-5 Lunar Sample in an External Electric Field - Junping Gu; Xiaoyu Qian; Yiwei Liu; Qinggong Wang; Yiyang Zhang; Xuan Ruan; Xiangjin Deng; Yaowen Lu; Jian Song; Hui Zhang; Yunning Dong; Mengmeng Wei; et al. (Engineering, 2024)
Facing the challenges of in-situ utilization of lunar regolith resources, applying an external electric field to manipulate lunar particles has become a promising method for space particle control, which mainly depends on the particle charging properties in the applied electric field. Using the surficial lunar regolith samples brought back from the Moon by the Chang’e-5 mission (CE5 LS), this work successively studied their charging properties, particle dynamics, and their collision damages to aerospace materials under the action of an external electric field in high-vacuum conditions. The results indicated that the charging process and electrostatic projection of lunar regolith particles under high-vacuum conditions were different from those under atmosphere conditions. The particle diameter range of CE5 LS used in the experiment is 27.7–139.0 μm. For electric field strength of 3–12 kV·cm−1, the charge obtained by CE5 LS is 4.8 × 10−15–4.7 × 10−13 C and the charge-to-mass ratio is 1.2 × 10−5–6.8 × 10−4 C·kg−1. The CE5 LS is easier to be negatively charged in an external electric field. Furthermore, significant damages were observed on the target impact surfaces, indicating severe influences of lunar regolith particles on aerospace materials. Our work contributes to a more comprehensive understanding of physical mechanisms controlling the lunar regolith shielding and utilization, and will inspire broad efforts to develop the lunar in-situ engineering solutions.